Need for care to caregivers: Psychological distress and its socio-demographic correlates among the relatives of persons with mental illness - Pathak, Abhijit (International Journal of Psychosocial Rehabilitation, 2017)
Background: The present study aims to compare the presence of psychological distress and its socio- demographic correlates among relatives of patients with mental illness and general public in Jharkhand. Methods: 240 relatives of persons with mental illness and 240 general public were assessed for psychological distress using Kessler Psychological Distress Scale version 10 (K10).Results: Psychological distress found among half of the total respondents at various levels. Relatives group reported higher levels of psychological distress than general public. The Spearman rank correlation shows significant positive correlation between psychological distress and gender, age, marital status and significant negative correlation between education, occupation and annual income.Conclusion: The study reveals psychological distress is significantly higher among the relatives group. It indicates the need for support and guidance to the caregivers of persons with mental illness. More comprehensive strategies are necessary to sensitize individuals about broad aspects of mental health and motivating them for approaching treatment. At the same time there is also need for strategies to provide affordable and accessible care to the needy.